Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I'm trying to understand the setup given in Multiscale analytical solutions and homogenization of n-dimensional generalized elliptic equations, pg 41:

Given the boundary value problem:

$$\frac{d}{dx}\left( -K(x)\frac{du}{dx}\right)=0\text{ in } \Omega\equiv(0,1)$$ $$u(0)=0$$ $$u(1)=1$$ where $K(x)$ is a smooth, strictly positive function in $\Omega$.

We can consider the quantity $q^0 \equiv -K(x)\frac{du}{dx}$ to be a constant in $\Omega$, since the equation specifically states that $\frac{d}{dx}\left( q^0\right)=0$. I understand that we can write:

$$\frac{du}{dx}=-\frac{q^0}{K(x)}$$ $$\Rightarrow u=\int_0^x -\frac{q^0}{K(\tau)} d\tau$$.

But the author claims that we can further rewrite this as:

$$u=K^0\int_0^x\frac{d\tau}{K(\tau)}$$ where $$K^0=-q^0=\frac{1}{\int_0^1 \frac{d\tau}{K(\tau)}}$$.

It is not immediately apparent from the given information that we can deduce that $-q^0=\frac{1}{\int_0^1 \frac{d\tau}{K(\tau)}}$. How could I have derived this from the given information?

share|cite|improve this question
up vote 2 down vote accepted

Plug the second boundary condition $u(1)=1$ into your formula $$u=\int_0^x -\frac{q^0}{K(\tau)} d\tau$$

share|cite|improve this answer
    
Oh, I see now... It was staring at me in my face and I didn't even realize it. So, using the derived formula, I can simply apply the condition $u(1)=1$ into the formula and solve for $-q_0$. I can't believe it was that simple! Thanks, PavelM. – Paul Jan 9 '13 at 5:34

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.